2015
DOI: 10.1016/j.phrp.2014.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Mycobacterium tuberculosis Early Secreted Antigenic Target 6 Recombinant Protein as a Diagnostic Marker in Skin Test

Abstract: ObjectivesTuberculosis (TB) is the leading infectious disease in the developing world. Delayed-type hypersensitivity skin test diagnoses TB using tuberculin purified protein derivative (PPD), but this test is incapable of distinguishing Mycobacterium tuberculosis (MTB) infection from bacillus Calmette–Guérin (BCG) vaccination or an infection caused by nontuberculous mycobacteria (NTM). This study was performed to evaluate the use of recombinant early secretory antigenic target 6 (rESAT-6), a secretory protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…A study in Iran also showed that the recombinant early secretory antigenic target 6 is more specific marker to detect of Mycobacterium tuberculosis infection than Tuberculin skin test [18]. In our study 38 cases (32%) did not have a BCG scar and PPD test was negative in these cases.…”
Section: Discussionsupporting
confidence: 45%
“…A study in Iran also showed that the recombinant early secretory antigenic target 6 is more specific marker to detect of Mycobacterium tuberculosis infection than Tuberculin skin test [18]. In our study 38 cases (32%) did not have a BCG scar and PPD test was negative in these cases.…”
Section: Discussionsupporting
confidence: 45%
“…Importantly, others and we have demonstrated that the MM thickness is around 7–8 nm 6 , 8 despite the presence of the very long chain of MA (up to C90), which raises important questions about the exact native conformation of MA. This outer membrane is also supposed to contain porins for the uptake of small hydrophilic molecules – porins characterized only in the case of M. smegmatis ( Msm ) 16 and membrane machineries involved in the secretion of virulence factors such as the well described ESAT-6 and Cfp10 proteins 17 19 , whose mechanism of translocation across the MM remains largely unknown. In contrast to the OL and MM, the PM has been well studied and proved to be similar of those to other microorganisms 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Of note, in spite of their individual variability in terms of induration size and duration, the animal model displayed highly reproducible. Moreover, several studies have also demonstrated that injection of PPD in guinea pigs was highly sensitive to infection (Dharmadhikari et al, 2011;Moradi et al, 2015) and developed strong TST after infection with Mtb (Kalra et al, 2010). The clinical and pathological changes observed in the infected guinea pigs were similar to those infected through the respiratory or subcutaneous routes in guinea pigs.…”
Section: Discussionmentioning
confidence: 99%